PENDIDIK PROFESIONAL DALAM PERSPEKTIF AL QURAN DAN HADIST - Ismael, Fauzan; AM, Rusydi; Charles, Charles (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of writing this article is to provide an overview of the role of professional educators in the Qur'an. In Islam, all work must be done professionally in the sense that it must be done correctly. Only professionals can do this. for this reason, writing this article will examine professional teachers in the Koran and Hadith as a guide for human life in this upfront. This research method is a qualitative research with a literature study approach. Teacher professionalism in the Koran shows that teachers must have democratic characteristics, be patient and gentle in carrying out their noble duties, forgive and be consistent in their duties and responsibilities, be able to work together (cooperatively) and be compassionate both in action and in the form of prayer. In addition, professional teachers are also required to be able to understand the psychology of students, emulate the manners of Rasulullah SAW in the learning process and master knowledge in their field.